O livro depois do livro : a experiência literária hipertextual em Giselle Beiguelman - Silva, Luciana Cristina Lourenço da (2007)
The present study intends to contribute for the reflections concerning the hypertextual narratives literary present in Internet. The focus of the research is Giselle Beiguelman's hypertextual poetic project focused in the book O livro depois do livro, present in the experimental site Desvirtual (www.desvirtual.com). The study was done through the analysis of the books O livro depois do livro " by Giselle Beiguelman, O Rinoceronte de Clarice" by Silas Corrêa Leite and "Miséria e grandeza do amor de Benedita by João Ubaldo Ribeiro. Starting from Charles Sanders Peirce s semiotics, we tried to understand as the literature is inserted in this process and how this process interferes in the construction of a reading of fruition aesthetic active in virtual atmosphere.